2022
DOI: 10.1155/2022/2651105
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Inflammation-Related Gene Signature for Overall Survival Prediction and Comprehensive Analysis in Pediatric Patients with Wilms Tumor

Abstract: Wilms tumor (WT) is a common pediatric renal cancer, with a poor prognosis and high-risk recurrence in some patients. The inflammatory microenvironment is gradually gaining attention in WT. In this study, novel inflammation-related signatures and prognostic model were explored and integrated using bioinformatics analysis. The mRNA profile of pediatric patients with WT and inflammation-related genes (IRGs) were acquired from Therapeutically Available Research to Generate Effective Treatments (TARGET) and Gene S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For exploring more potential inflammatory response-related targets and mechanisms in development of tumor, similar risk models were successfully constructed in many cancers, such as nephroblastoma and bladder cancer [ 29 , 30 ]. Inflammatory diseases are linked to lncRNAs, which might be used as biomarkers to diagnose inflammatory diseases such as rheumatoid arthritis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For exploring more potential inflammatory response-related targets and mechanisms in development of tumor, similar risk models were successfully constructed in many cancers, such as nephroblastoma and bladder cancer [ 29 , 30 ]. Inflammatory diseases are linked to lncRNAs, which might be used as biomarkers to diagnose inflammatory diseases such as rheumatoid arthritis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies also found that BICC1’s aberrant expression contributes to the development of other malignant tumors: oral cancer, Wilms tumor and non-small cell lung cancer [ 14 , 15 ]. However, He et al [ 16 ] only found that BICC1 is a prognosis related gene of pancreatic ductal adenocarcinoma. How BICC1 promotes PC the occurrence, development, and associated biological behavior remains uncertain.…”
Section: Introductionmentioning
confidence: 99%